If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -6x = 7 + 5 Combine like terms: 7 + 5 = 12 18 + -6x = 12 Solving 18 + -6x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -6x = 12 + -18 Combine like terms: 18 + -18 = 0 0 + -6x = 12 + -18 -6x = 12 + -18 Combine like terms: 12 + -18 = -6 -6x = -6 Divide each side by '-6'. x = 1 Simplifying x = 1
| 0.19/1.577 | | -8v+28.9=3.3 | | -14.6=-2.1+w/5 | | 4x+3x-9x=60-2x-13 | | 8+x/17.92=15 | | 3x-6[4x+2(x+1)]=-12 | | 5x+138=11x-6 | | 3v-2.6=2.2 | | -3.6=v/4+9.2 | | 7.68=3u | | 0.5714x-5=3 | | 7=w/22.4 | | 4x-15=3-5x | | 2x^2-18x=-16 | | 0.8x+6.1=1.7 | | x/-5=10 | | 8-7x-2=-6+4x-10 | | 7p-2(3p+4)= | | 3x-6-4x-12=2x | | 4y-2(y-2)+5= | | 4x+18=3+8x-5 | | |-6|-|10-3|= | | 1/2+(-5/8) | | 2x+9=-97-10x | | 2/3p+1=-7 | | 5-2x+x=-10 | | 2/3+1=-7 | | -6(8m+7)= | | 7675483920129834765434x=5 | | 11-7x=59-28x | | -4x-12=-16-3x | | x^2+8x=4x |